2006
DOI: 10.1007/s10517-006-0403-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo differentiation of mesenchymal stem cells in the cardiomyocyte direction

Abstract: The possibility of mesenchymal stem cell differentiation in the cardiomyocyte direction was studied on Wistar-Kyoto rats with myocardial infarction induced by ligation of the left coronary artery. In vitro treatment of mesenchymal stem cells with 5-azacitidine led to spontaneous contractions of about 15% cells in culture. Analysis of the expression of matrix RNA showed expression of fetal and functional markers of the myocardium in this cell culture. In vivo on day 21 after myocardial infarction and intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Although it is not feasible to evaluate the possibility of differentiation along every possible cell line that has been reported for MSCs, it clearly shows that their multilineage potential is preserved after uptake of the OxySpin probes. While recent evidence indicates that paracrine-signaling effects of MSC transplantation are the primary reason for therapeutic efficacy (10,12,30), the possibility remains that, under appropriate circumstances, MSCs may be capable of differentiation to cardiomyocyte-like cells in vivo (16,19). If so, future studies may demonstrate that MSCs transplanted to the ischemic myocardium may be critical on both fronts, through paracrinesignaling effects and the attenuation of ventricular wall thinning and cardiac remodeling through differentiation into car- No MI was induced in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not feasible to evaluate the possibility of differentiation along every possible cell line that has been reported for MSCs, it clearly shows that their multilineage potential is preserved after uptake of the OxySpin probes. While recent evidence indicates that paracrine-signaling effects of MSC transplantation are the primary reason for therapeutic efficacy (10,12,30), the possibility remains that, under appropriate circumstances, MSCs may be capable of differentiation to cardiomyocyte-like cells in vivo (16,19). If so, future studies may demonstrate that MSCs transplanted to the ischemic myocardium may be critical on both fronts, through paracrinesignaling effects and the attenuation of ventricular wall thinning and cardiac remodeling through differentiation into car- No MI was induced in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have the potential to differentiate into cells of vascular lineages, including smooth muscle and endothelial cells. MSCs have the capacity to differentiate into cardiomyocyte-like cells in vitro (1), although it has been observed to be a rare event in in vivo studies (2,8,19,31). The effectiveness of MSC-based stem cell therapy has been attributed more to the paracrine-signaling properties of these cells, rather than to their differentiation abilities (12,30).…”
mentioning
confidence: 99%
“…MSCs can differentiate into different cell lineages such as bone, fat and cardiac muscle-like cells upon different stimuli. Recent evidences have suggested that MSCs can differentiate into cardiomyogenic cells in vivo or in vitro (Toma et al, 2002;Kruglyakov et al, 2006;Cho et al, 2009;Tan et al, 2009), therefore hold the potential to become the donor source of myocardial cells for cell therapy in clinical treatment of myocardial infarction, and provide one final solution to the problem of inadequate donor cells for clinical use . However, Chemical inductors, such as 5-azacytidine (5-aza), which was commonly used as cardiomyocyte differentiation inductor in previous studies, may have cytotoxic side effects that may damage cells over time.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells have the potential to differentiate into mature cardiac cells or promote native repair through angiogenesis, recruitment of host SCs, or induction of myocytes into the cell cycle (Kruglyakov et al 2006;Ohnishi et al 2007;Amado et al 2005;Mangi et al 2003). It is believed that the multifaceted paracrine actions of MSCs explain, at least in part, their tissue-healing properties (Caplan and Dennis 2006;Dai et al 2005;Gnecchi et al 2006;Kinnaird et al 2004).…”
Section: Introductionmentioning
confidence: 99%